REVITALISASI KAWASAN BERSEJARAH SEBAGAI WARISAN BUDAYA DI KOTA WATAMPONE KABUPATEN BONE - Widyaningsih, Wiwied; Ersina, Sriany (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2015)
Watampone Bone is downtown district which has a variety of cultural heritage, in the form of goods, objects, and areas that have historical value. This happens because the district Bone is one of the great kingdom in the archipelago in the past, characterized by the statue of Whitewater Palakka established in 1991. Based on the existing historical, this place became the center of a tourist destination, relax and socialize. However, the condition of the area is currently experiencing a setback, there is physical damage to the region, the region that does not change the function as intended, so it does not fully meet the needs of the community. To answer the needs of the surrounding community, then the revitalization of the historic district as a cultural heritage in the City Watampone. Revitalization of this area use the theme Arung Palakka Butta region. This theme is based on the history of the area. On this theme determined the form in which all the physical design refers to the form. Forms, namely: umbrellas, Spear, Sokko Racca and Balla Soba (Sauroja). This form has a special meaning for Whitewater Palakka and regions. This is done to create an area that has the image of the region.